Utilizing Retrieval Augmented Generation (RAG)-Based Chatbots as an Innovative Learning Tool in Higher Education: A Case Study on the Use of Digital Learning Resources - Murti, Yusza; Ramadhani, Dian Puteri; Irawan, Herry (CV. Media Inti Teknologi, 2025)
Background: Higher education institutions face information fragmentation and cognitive overload as students struggle to access learning materials scattered across multiple digital platforms. Large Language Models encounter hallucination issues and static knowledge bases, limiting their educational application.Aims: This research aims to design and evaluate a Retrieval Augmented Generation (RAG)-based chatbot system integrated with Learning Management Systems to address information fragmentation in educational environmentsMethods: We employed Design Science Research Methodology (DSRM) to develop the RAG-based chatbot. Technology Acceptance Model (TAM) assessment with 267 undergraduate students and semi-structured interviews with five faculty members evaluate user acceptance and pedagogical perspectives.Results: The RAG chatbot achieved strong initial user acceptance (mean score 4.097). Students valued perceived usefulness over ease of use, with high usage intentions and recommendation willingness. Faculty recognized pedagogical value while emphasizing quality assurance needs.Conclusion: This exploratory study demonstrates technical feasibility and baseline user acceptance for RAG-based chatbots in education, showing promise for addressing information accessibility challenges. Demonstration-based evaluation requires validation through longitudinal field studies.